The Impact of Clinical and Cognitive Variables on Social Functioning in Parkinson's Disease: Patient versus Examiner Estimates - Patrick McNamara; Karina Stavitsky; Raymon Durso; Erica Harris (Parkinson's Disease)
Purpose. To assess the impact of clinical variables on social skills and behaviors in Parkinson's disease (PD) patients and patient versus examiner estimates of social functioning. Methods. Twenty-eight patients with PD and 32 controls with chronic disease were assessed with a battery of neuropsychologic, personality, mood, and social function tests. Results. Patients' estimates of their own social functioning were not significantly different from examiners' estimates. The impact of clinical variables on social functioning in PD revealed depression to be the strongest association of social functioning in PD on both the patient and the examiner version of the Social Adaptation Self-Evaluation Scale. Conclusions. PD patients appear to be well aware of their social strengths and weaknesses. Depression and motor symptom severity are significant predictors of both self- and examiner reported social functioning in patients with PD. Assessment and treatment of depression in patients with PD may improve social functioning and overall quality of life.